2018
DOI: 10.1093/pch/pxy163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music (Brahms lullaby) and non-nutritive sucking on heel lance in preterm infants: A randomized controlled crossover trial

Abstract: The abnormal HR total number was significantly lower in the intervention group (2) than in the standard care group (23) (frequency ratio=0.087, P<0.0001). 3) Figure 2 was incorrect and has since been corrected in the article. The correct Figure 2 is shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Discrepancies were resolved by discussion and consensus. The overall results showed that 27 RCTs had a low (69.2%), 17‐43 7 had a moderate (17.9%) 44‐50 and 5 had a high (12.8%) risk of bias 51‐55 …”
Section: Resultsmentioning
confidence: 98%
“…Discrepancies were resolved by discussion and consensus. The overall results showed that 27 RCTs had a low (69.2%), 17‐43 7 had a moderate (17.9%) 44‐50 and 5 had a high (12.8%) risk of bias 51‐55 …”
Section: Resultsmentioning
confidence: 98%
“…Effect of music with NNS, FT, and holding group showed more effective in PIPP scores, heart rate, oxygen saturation and abnormal heart rate for neonatal pain. 31 Combined music and touch therapy proved more effective than control group for late preterm infants on painful scores. 32 Using a combination of them, such as sucrose and radiant warmth group, sucrose with NNS group, music, NNS and FT group can obtain better effectiveness.…”
Section: Pain Management: Non-pharmaceutical Interventions For Neonatal Painmentioning
confidence: 95%
“…32 Using a combination of them, such as sucrose and radiant warmth group, sucrose with NNS group, music, NNS and FT group can obtain better effectiveness. 10, 13,31,33 Moreover, SS is a combination of sensory stimuli, hence is a good method and may be more useful than single stimulus.…”
Section: Pain Management: Non-pharmaceutical Interventions For Neonatal Painmentioning
confidence: 99%
“…Исследования, которые были проведены в неонатологических отделениях интенсивной терапии, подтверждают, что использование музыки или пения у недоношенных детей может положительно влиять на следующие ключевые области: стабилизацию физиологических функций (Rajeshri, Jayendra, Rhushita, & Tushar, 2016;Bieleninik, Ghetti, & Gold, 2016;Arnon et al, 2014;Loewy, Stewart, Dassler, Telsey, & Homel, 2013;Standley, 2012)), прием пищи (Efendi & Tane, 2019;Rajeshri, Jayendra, Rhushita, & Tushar, 2016;Bieleninik et al, 2016;Yildiz & Arikan, 2011;Whipple, 2008), прибавку в весе (Rajeshri, Jayendra, Rhushita, & Tushar, 2016;Bieleninik et al, 2016;Kemper & Hamilton, 2008)), восстановление после болезненных процедур (Uematsu & Sobue, 2019;Tramo et al, 2011;Hartling et al, 2009 ), качество сна (Bieleninik et al, 2016;Arnon et al, 2006), когнитивные процессы и неврологический исход (Lordier et al, 2019;Haslbeck, 2012;Standley & Walworth, 2010).…”
Section: Literature Reviewunclassified